The Prognostic Significance of the Systemic Inflammation Response Index (SIRI) and HALP Score in Hodgkin's Lymphoma - Oral, Kübra; Uysal, Ayşe (Mdpi, 2026)
Objective: This study aimed to evaluate the prognostic significance of lymphocyte-associated inflammatory markers and the HALP score in patients with Hodgkin's lymphoma. Methods: This was a retrospective study that included patients who were diagnosed with Hodgkin's lymphoma and followed up between 2004 and 2024. The inflammatory markers (NLR, PLR, MLR, SII, SIRI, and PIV) and HALP score were calculated from the patients' biochemical and hematological parameters, and the relationship between these parameters and stage, spleen and liver involvement, relapse, mortality, overall survival, and progression-free survival was analyzed. Results: A total of 117 patients were included, and multivariate analysis indicated that progression-free survival was statistically and significantly associated with treatment type (p = 0.0285), PLR (p = 0.0188), and PIV (p = 0.0297). In terms of overall survival, age (p = 0.0011), treatment type (p = 0.0108), and SIRI (p = 0.0108) remained as statistically significant predictors. Although the HALP score showed a significant association with PFS in the univariate analysis (p = 0.0104), this association did not persist in the multivariate model. In addition, no statistically significant relationship between the HALP score and OS was observed in either the univariate or multivariate analysis. Conclusions: The SIRI is a prognostic marker in Hodgkin's lymphoma and may be useful for predicting overall survival.
Keywords: Hodgkin's lymphoma; systemic inflammation response index (SIRI); HALP score